Power Negotiation and Identity: Socio-Economic Transformation of Ethnic Minorities Through Biogas Empowerment in Central Lampung - Transada, Iklas (Potret Pemikiran, 2024)
This study examines the impact of a biogas and silage empowerment program on the socio-economic transformation and power negotiation of the ethnic minority community in Rukti Endah Village, Central Lampung, Indonesia. Through a qualitative approach combining critical ethnography and conventional data collection methods, this research analyzes changes in energy consumption patterns, increases in farmers' productivity and welfare, social impacts on quality of life and women's empowerment, and the program's influence on power dynamics and minority identity. The findings reveal that the adoption of sustainable technology not only improves material well-being but also strengthens the community's bargaining position and cultural identity within the broader society. The empowerment program enables the minority community to become active agents of change, contributing to a more inclusive and equitable social structure. This research highlights the transformative potential of environmentally friendly technology when applied with a socio-culturally sensitive approach, offering valuable insights for policymakers and development practitioners working on community empowerment in diverse contexts. However, the study also underscores the complexities and challenges involved in the empowerment process, emphasizing the need for continuous efforts to ensure fair distribution of benefits and the integration of local wisdom in sustainable development initiatives.